Comparative investigation of ferromagnetic hysteresis properties of ising and heisenberg thin-films: The mean-field analysis - Chumpol Supatutkul (2018)
© 2017, Chiang Mai University. All rights reserved. In this work, magnetic properties of Ising and Heisenberg thin-films placed under influences of external magnetic field and temperature perturbations were investigated using mean-field theory. The aim of the study was to investigate the ferromagnetic critical behavior with an emphasis on dynamic phase transition. The zero external field results show that the Heisenberg films have critical temperatures lower than those of the Ising films considered at the same film thickness. On the other hand, with periodic magnetic field turning on, the dynamic phase transition boundaries between asymmetric and symmetric phases were extracted to construct dynamic phase transition diagram, where field amplitude, field frequency, temperature and film thickness were all found to have strong influences on the characteristic of the dynamic phase boundaries. Though both Ising and Heisenberg films give qualitatively the same diagram, the Heisenberg has smaller asymmetric phase regions. This implies that, both static and dynamic phase transition requires less thermal or magnetic energy in the Heisenberg model than that in the Ising model, due to the anisotropic characteristic of the Ising model. Therefore, from these results, one can use the dynamic phase transition diagrams and hysteresis characteristics as guidelines in designing magnetic applications with desired functionalities. Either Ising or Heisenberg models should be considered for a particular application depends on the anisotropic requirements of that application.